2016
DOI: 10.1007/s00170-016-9780-0
|View full text |Cite
|
Sign up to set email alerts
|

Extension of process damping to milling with low radial immersion

Abstract: This paper investigates the stabilizing effect of process damping at low cutting speeds for regenerative machine tool vibrations of milling processes. The process damping is induced by a velocity-dependent cutting force model, which takes into account that the actual cutting velocity is different from the nominal one during machine tool vibrations. The chip thickness and the cutting force are calculated according to the direction of the actual cutting velocity. This results in an additional damping term in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Another approach, which is also used in this paper, follows the research of Das and Tobias [13], who showed that even static models can be used to model process damping by more accurately considering the geometry of the cut with respect to the instantaneous direction of the cutting speed including vibration. This approach was applied, for example, by Molnar and Bachrathy [4,27] to cylindrical milling. One of the main complications of this approach, which this paper aims to address, is the integration of damping contributions for geometrically complex cutting edges where the local face and blade inclination angles change gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach, which is also used in this paper, follows the research of Das and Tobias [13], who showed that even static models can be used to model process damping by more accurately considering the geometry of the cut with respect to the instantaneous direction of the cutting speed including vibration. This approach was applied, for example, by Molnar and Bachrathy [4,27] to cylindrical milling. One of the main complications of this approach, which this paper aims to address, is the integration of damping contributions for geometrically complex cutting edges where the local face and blade inclination angles change gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Altintas considered cutting speed and acceleration to influence the curvature of the machining surface (Altintas, 2012; Altintas et al, 2008). Altintas model was updated by Turkes et al (2012); Yang et al (2016); Zhu et al (2017); Molnar et al (2017); and Feng et al (2018). The process damping is composed by applying shear angle oscillation, and change in cutting force, where a process damping ratio was generated by Turkes et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al (2017) developed the energy-based model for stability analysis and process damping identification. Molnar et al (2017) considered a velocity-dependent process damping in orthogonal cutting that differentiates between the actual cutting and nominal cutting during machine vibration. Furthermore, the plowing forces influence power spectral density and process damping through the cutter signal (Feng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When the rate of energy supply is overbearing on the rate of energy dissipation instability grows. Process damping is a very helpful phenomenon at low speeds because it considerably enhances damping thus improving stability [17, 18].…”
Section: Introductionmentioning
confidence: 99%